N-Glycosylation of Lipocalin 2 Is Not Required for Secretion or Exosome Targeting - Borkham-Kamphorst, Erawan; Van de Leur, Eddy; Meurer, Steffen K.; Buhl, Eva M.; Weiskirchen, Ralf (Frontiers in Pharmacology, 2018)
Lipocalin 2 (LCN2) is a highly conserved secreted adipokine acting as a serum transport protein for small hydrophobic molecules such as fatty acids and steroids. In addition, LCN2 limits bacterial growth by sequestering iron-containing siderophores and further protects against intestinal inflammation and tumorigenesis associated with alterations in the microbiota. Human LCN2 contains one N-glycosylation site conserved in other species. It was postulated that this post-translational modification could facilitate protein folding, protects from proteolysis, is required for proper trafficking from the Golgi apparatus to the cell surface, and might be relevant for effective secretion. We here show that the homologous nucleoside antibiotic tunicamycin blocks N-linked glycosylation but not secretion of LCN2 in primary murine hepatocytes, derivatives thereof, human lung carcinoma cell line A549, and human prostate cancer cell line PC-3. Moreover, both the glycosylated and the non-glycosylated LCN2 variants are equally targeted to exosomes, demonstrating that this post-translational modification is not necessary for proper trafficking of LCN2 into these membranous extracellular vesicles. Furthermore, a hydrophobic cluster analysis revealed that the N-glycosylation site is embedded in a highly hydrophobic evolutionarily conserved surrounding. In sum, our data indicate that the N-glycosylation of LCN2 is not required for proper secretion and exosome cargo recruitment in different cell types, but might be relevant to increase overall solubility.